The making of Indo-Persian culture : Indian and French studies - Gaborieau, Marc.; Nalini, Françoise Delvoye; Alam, Muzaffar, 1947- (New Delhi : Manohar Publishers & Distributors, 2000)
Seminar papers.
Includes bibliographical references and indexes.
Mode of access: Internet.
Keywords: Iran -- Relations -- India -- Congresses; India -- Relations -- Iran -- Congresses; India -- Civilization -- Iranian influences -- Congresses